Fair design and use of the budgetary process and managerial performance - Santos, Vanderlei dos; Beuren, Ilse Maria; Marques, Leandro (Revista Contabilidade & Finanças, 2023)
This study analyzes the impacts of the fair design and use of the budgetary process, from the perspectives of formal and informal justice, on fairness judgments, on budgetary participation, and on managerial performance. Complementarily, it also analyzes the mediating effect. Research on the impacts of budgetary participation on managerial performance presents conflicting and inconclusive evidence. The studies on organizational justice, in turn, mainly focus on individual perceptions of justice, from a descriptive and perceptual perspective, not considering the normative approach, and treating justice rules and fairness judgments as synonymous. That segregation is relevant as it reinforces the importance of the fair design and use of the budgetary process, going beyond considering individual fairness judgments. The research revealed that the fair design and use of the budgetary process influence managerial performance; however, the individual perception of justice (fairness judgments) did not exert a direct influence. These findings are relevant because they highlight the impacts of justice in terms of the effects that a system generates, not only considering individual perceptions. A survey was conducted with a random sample of 110 managers chosen using the LinkedIn social network. For the data analysis, the structural equations modeling technique was applied. The study contributes to the literature that examines behavioral aspects of the relationship between budgetary participation and managerial performance, by seeking to understand in which conditions budgetary participation results in better performance. In this research, these relationships are analyzed in light of the foundations of justice, from the perspective of justice rules and fairness judgments. The evidence suggests that budgetary participation affects managerial performance when it results from the fair design and use of the budgetary process.